Rapid regulations of metabolic reactions in Escherichia coli via light‐responsive enzyme redistribution. Issue 9 (10th June 2022) - Huang, Zikang; Sun, Lize; Lu, Genzhe; Liu, Hongrui; Zhai, Zihan; Feng, Site; Gao, Ji; Chen, Chunyu; Qing, Chuheng; Fang, Meng; Chen, Bowen; Fu, Jiale; et al.
Abstract: Protein‐based condensates have been proposed to accelerate biochemical reactions by enriching reactants and enzymes simultaneously. Here, we engineered those condensates into a photo‐activated switch in Escherichia coli (PhASE) to regulate enzymatic reactions via tuning the spatial correlation of enzymes and substrates. In this system, scaffold proteins undergo liquid–liquid phase separation (LLPS) to form light‐responsive compartments. Tethered with a light‐responsive protein, enzymes of interest (EOIs) can be recruited by those compartments from cytosol within only a few seconds after a pulse of light induction and fully released in 15 min. Furthermore, we managed to enrich small molecular substrates simultaneously with enzymes in the compartments and achieved the acceleration of luciferin and catechol oxidation by 2.3‐ and 1.6‐folds, respectively. We also developed a quantitative model to guide the further optimization of this demixed regulatory system. Our tool can thus be used to study the rapid redistribution of proteins, and reversibly regulate enzymatic reactions in E. coli . Graphical Abstract and Lay Summary: Strategies for rapid regulation of enzymatic reactions in E. coli are still in their infancy. The authors constructed protein phase separation‐based compartment and utilized optogenetic protein interaction to enable rapid and reversible enzyme recruitment by the compartment. The feasibility for controlling the reaction efficiency by tuning spatial distribution of enzymes has been demonstrated in two special cases: Renilla luciferase reporter assay and catechol oxidation assay.